Assessment the Shear Behavior of Sustainable Thick Hollow Core Slab Using Experimental and Nonlinear Finite Element Modelling - Sabr, Yousif Nassif; Jarallah, Dr. Husain Khalaf (Anbar Journal of Engineering Sciences, 2019)
This investigation provides experimental results and nonlinear analysis by using finite element model of thick hollow core slab made from recycled lightweight material. Four hollow core slabs specimens were cast and tested in this investigation with dimensions (1200mm length, 450mm width and 250mm thickness). The crushed clay brick was used as a coarse aggregate instead of gravel. The iron powder waste and silica fume were used in order to increase the compressive strength of concrete. The techniques reduction hollow length and use shear reinforcement were used to improve shear strength and avoid shear failure. The specimens were tested by applying two-line load up to failure. The experimental results were showed these techniques were resisted the shear failure significantly and works to change failure mode from shear to flexural failure. Finite element computer software program (ANSYS) was used to analysis hollow core slabs specimens and compare the experimental results with the theoretical results. Good agreement have been obtained between experimental and numerical results.